Evaluation Of The Implementation Of Digital Transformation Policy In Improving The Quality Of Public Services In Local Government: A Study On The Smart City Program Of Makassar City - Muhammad Ridha Suaib; Syamsuddin Maldun; Juharni Juharni (Jurnal Ilmiah Mandala Education (JIME), 2026)
Digital transformation has become a primary strategy for local governments to improve the quality of public services, particularly through the implementation of the Smart City program. However, the success of this policy is not solely determined by technology adoption, but also by how the digital transformation policy is implemented in governance practices. This study aims to evaluate the implementation of the digital transformation policy in improving the quality of public services in the Makassar City Government through the Smart City program. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the implementation of the Smart City policy in Makassar City has encouraged increased efficiency and accessibility of public services, but has not yet fully generated optimal public value. The main challenges lie in the limited capacity of human resources of the apparatus, fragmented coordination between regional agencies, and the digital literacy gap in the community. This study confirms that digital transformation in public services is an institutional process that requires policy integration, digital leadership, and an orientation towards public value. Theoretically, this study contributes to the enrichment of public policy implementation studies by integrating the perspectives of e-government, public value, and good governance in the context of Smart City. Practically, the findings of this study provide strategic recommendations for local governments in designing and evaluating more inclusive, accountable, and sustainable digital transformation policies.